Interpretability of the quality of life in hand eczema questionnaire - Oosterhaven, Jart; Ofenloch, Robert; Schuttelaar, Marie L.A. (The journal of investigative dermatology, 2020)
The Quality Of Life in Hand Eczema Questionnaire (QOLHEQ) is used to measure impairment of health-related quality of life in hand eczema. Here, we prospectively studied the interpretability of international QOLHEQ scores at three time points: baseline, after 1-3 days (T1), and after 4-12 weeks (T2). Adult patients with hand eczema completed the QOLHEQ and anchor questions for overall assessment of health-related quality of life impairment. Interpretability of single scores was assessed at baseline by defining severity bands based on agreement with the anchor questions. Smallest detectable change was calculated at T1. Minimally important change of improvement was calculated at T2 using three methods: mean cut-off, receiver operating characteristic, and 95% limit. A total of 294 adult patients were included (160 males, mean age 44.9 years). The final proposed severity band of overall QOLHEQ single scores (κ-coefficient of agreement, 0.431) was not at all, 0-10; slightly, 11-39; moderately, 40-61; strongly, 62-86; and very strongly, ≥87. Separate overall severity bands were proposed for males and females and the four subscales of the QOLHEQ. The smallest detectable change in 166 unchanged patients was 18.6 points. The preferred minimally important change, obtained with the receiver operating characteristic method, was 21.5 points. An overall QOLHEQ score of ≥22 is recommended as cut-off for a minimally important, real change.